MODIFIED CARBON PASTE ELECTRODE BY BAGASSE FOR CR(VI) ANALYSIS WITH VOLTAMMETRY - Maydah, Gracella
Environmental pollution is one of the complex problems in human life. One of the causes of environmental pollution is due to heavy metal contamination from industrial waste. Chromium metal is one of heavy metal. In the environment, chromium metal is present in the form of Cr(III) and Cr(VI). Cr(VI) has toxic, corrosive, and carcinogenic properties compared to Cr(III). In recent years, the development of sensitive and selective sensors for analyzing heavy metals has continued due to the high demand for quantification and detoxification of toxic metals at lower concentration levels in environmental samples. Agricultural products have an important role to play as sensors that are effective, efficient, low cost, and environment friendly. One of the agricultural products that can be used is bagasse. The purpose of this study was to modify carbon paste electrode with bagasse and determine its performance for Cr(VI) analysis using voltammetry techniques. The results showed that the use of bagasse can increase the sensitivity of Carbon Paste Electrode (CPE) in measuring Cr(VI). The highest sensitivity was obtained on measurements using modified CPE with a composition of 5% (w/w) bagasse. From several voltammetry techniques used, the highest sensitivity was obtained in measurements using the cyclic stripping voltammetry technique with an optimum deposition potential of 1100 mV and an optimum deposition time of 350 s with 0,1 M HCl supporting electrolyte solution. Furthermore, it is necessary to determine the electrode performance by measuring the working area, limit. detection, reproducibility, and sample measurement. Based on the literature study, the working area of Cr(VI) measurement using the voltammetry method that has been developed is in the range 10-9 - 10-4 M with a detection limit of 10-9 M. Therefore, it is expected that the modified CPE with a composition of 5% bagasse (w/w) has a wide linear area and a low detection limit as shown in the literature study on Cr(VI) measurement.